Howler Monkeys 2014
DOI: 10.1007/978-1-4939-1957-4_9
|View full text |Cite
|
Sign up to set email alerts
|

The Howler Monkey as a Model for Exploring Host-Gut Microbiota Interactions in Primates

Abstract: The mammalian gut microbiota is essential to many aspects of host physiology, including nutrition, metabolic activity, and immune homeostasis. Despite the existence of numerous studies of the impact of the gut microbiota on human health and disease, much work remains to be done to improve our understanding of the host-microbe relationship in nonhuman primates. Howler monkeys ( Alouatta spp.) are highly dependent on the gut microbiota for the breakdown of plant structural carbohydrates, and in this chapter we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 137 publications
(124 reference statements)
1
12
0
Order By: Relevance
“…However, it appears from our data that Proteobacteria is a major component of white‐faced capuchin gut microbial communities and may play a large role in lipid metabolism in their gut microbiome. The white‐faced capuchin gut microbial community composition appears to be different than that of most primates studied to date, with a higher relative abundance of Proteobacteria and lower relative abundances of Bacteroidetes (Amato and Righini, ; Amato et al, ; Barelli et al, ; Bennett et al, ; Degnan et al, ; Frey et al, ; Hale, Tan, Knight, & Amato, ; Moeller et al, ; Ochman et al, ; Ren, Grieneisen, Alberts, Archie, & Wu, ; Su et al, ; Sun et al, ; Tung et al, ), with the caveat that the variation in methods between published studies makes a direct comparison difficult (Table ). There are, however, similarities in the gut microbiome between capuchins and pygmy lorises (Bo et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears from our data that Proteobacteria is a major component of white‐faced capuchin gut microbial communities and may play a large role in lipid metabolism in their gut microbiome. The white‐faced capuchin gut microbial community composition appears to be different than that of most primates studied to date, with a higher relative abundance of Proteobacteria and lower relative abundances of Bacteroidetes (Amato and Righini, ; Amato et al, ; Barelli et al, ; Bennett et al, ; Degnan et al, ; Frey et al, ; Hale, Tan, Knight, & Amato, ; Moeller et al, ; Ochman et al, ; Ren, Grieneisen, Alberts, Archie, & Wu, ; Su et al, ; Sun et al, ; Tung et al, ), with the caveat that the variation in methods between published studies makes a direct comparison difficult (Table ). There are, however, similarities in the gut microbiome between capuchins and pygmy lorises (Bo et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of additional bacterial glucocorticoid‐metabolizing enzymes have also been discovered (Devlin & Fischbach, ; Morris & Ridlon, ). Amato and Righini () suggest that it is possible for increased glucocorticoid levels to coincide with decreased microbial diversity, since primates in degraded habitats have reduced microbial diversity and presumably experience higher allostatic load. Although no primate study has yet tested this hypothesis, in wild red squirrels ( Tamiasciurus hudsonicus ) it was found that fecal glucocorticoid metabolites were negatively correlated with bacterial diversity and that there was a positive relationship over time between fecal glucocorticoid metabolite concentrations and bacterial abundance of Pasteurellaceae, a family with known epizootic pathogens (Stothart et al, ).…”
Section: Microbial Endocrinology Of the Stress Responsementioning
confidence: 99%
“…These shifts in the gut microbiota may be triggered by factors such as changes in host diet or hormone levels, and, if timed correctly, could help hosts compensate for energy shortfalls and changes in energy expenditure (Amato, ). Indeed, a study of Alouatta pigra found that reproductive state significantly altered gut microbial community structure (Amato & Righini, ; Nakamura et al, ; but see Ren, Grieneisen, Alberts, Archie, & Wu, ).…”
Section: Introductionmentioning
confidence: 99%